Spatial diversity of tourist function development: the municipalities of Poland’s West Pomerania province - Borzyszkowski, Jacek; Marczak, Mirosław; Zarębski, Patrycjusz (Acta geographica Slovenica, 2016)
This article examines the spatial diversity of tourist function development using the example of one of Poland’s sixteen main administrative regions: the West Pomerania Province (Polish: Województwo zachodniopomorskie). The analysis was carried out based on the values of the Defert tourist function index, which is one of the basic indexes used in tourism geography. The analysis demonstrated significant differences between the individual municipalities in the region examined. This confirms the assumption that seaside municipalities have the highest tourist function development.